If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9x + 1 = 2x + 64 Reorder the terms: 1 + 9x = 2x + 64 Reorder the terms: 1 + 9x = 64 + 2x Solving 1 + 9x = 64 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. 1 + 9x + -2x = 64 + 2x + -2x Combine like terms: 9x + -2x = 7x 1 + 7x = 64 + 2x + -2x Combine like terms: 2x + -2x = 0 1 + 7x = 64 + 0 1 + 7x = 64 Add '-1' to each side of the equation. 1 + -1 + 7x = 64 + -1 Combine like terms: 1 + -1 = 0 0 + 7x = 64 + -1 7x = 64 + -1 Combine like terms: 64 + -1 = 63 7x = 63 Divide each side by '7'. x = 9 Simplifying x = 9
| 2x-6=44-8x | | 7x+4=5x+37 | | 2x+6=44-8x | | 1/3(9a^2-15a+7) | | 7(7X+5)=11-(x-9) | | w+3/4=52/3 | | 17(k+921)=714 | | 8x=289 | | 3x=580 | | -19(t+-17)=608 | | x/7(x-14y-5) | | 2x+3(-8/10)=-4 | | 2x-4y=-18 | | 8+2f+f=44 | | 9+3=711 | | 2/-7x+8 | | y+11=4/5(x+12) | | 4y-1=15 | | A=2*pi*r*h | | x^22-1=0 | | 6(j+3)-23=49 | | 4x^2-56x+112=0 | | -1=-5(t-78)+69 | | 2n-3=16 | | -6(d-97)=-12 | | 268-4x=41x+18 | | 3x^2(x^2-8)+6x+5=4x^4-6x(4x-1)+4 | | 97=5(c-79)-2 | | 5-7x=38-28x | | 3(10-2)=(3*10)-(3*2) | | -7x+8/2 | | 9x-7x=18 |